From law to practice: Analyzing regulatory challenges in the context of Brazilians commercial pharmacies (Research, Society and Development, 2024)
In the world of commercial pharmacies, the intersection between legislation and daily practice is a constant challenge. While laws and regulations aim to ensure the quality, safety, and efficacy of pharmaceutical products, the enforcement of these regulations often presents obstacles in the commercial environment. This study aims to analyze the regulatory challenges faced by Brazilian commercial pharmacies. The methodological approach in the development of this study was integrative literature review, a method that allows the integration of knowledge through a methodical and rigorous process. Thus, 17 articles were selected as the basis for the production of this integrative review. Regulations require pharmacies to meet a series of technical, structural, and safety criteria, which can be challenging for commercial establishments. Therefore, the need to comply with all legal requirements, as well as to stay updated with the constant changes in regulations, makes the process of regularizing commercial pharmacies a complex task that demands constant attention and care from those responsible for the establishment. In conclusion, the process of regulating commercial pharmacies in Brazil is inherently complex and challenging, requiring a continuous commitment to regulatory compliance, education of professionals, and adaptation to legislative changes. Overcoming these challenges is crucial to ensure patient safety and the effectiveness of pharmaceutical services, promoting ethical and quality practice in the sector.